The role of angiopoietins 1 and 2 in the regulation of tumor angiogenesis - Kopczyńska, Ewa; Makarewicz, Roman; Tyrakowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2007)
Angiopoietins, besides growth factors, proteolytic enzymes and adhesive molecules, participate in angiogenesis, and also tumours. Angiopoietins 1 and 2 are ligands of the receptor tyrosine kinase Tie-2, specific for endothelial cells. The carboxy-terminal domain is responsible for receptor binding, while the amino-terminal domain enables multimerization of them, necessary for receptor activation. Angiopoietins 1 and 2 have similar ability to bind to receptor Tie-2, whereas Ang-1 is an agonist, and Ang-2 is an antagonist. Ang-1 activates the receptor by induction of tyrosine phosphorylation; protein kinases take part in signal cell transduction. However, Ang-2 inhibits this pathway. The functions of Ang-1 and Ang-2 in angiogenesis in principle are opposite. Ang-1 is responsible for vascular integrity, through stimulation of endothelial cell migration and adhesion, and inhibition of apoptosis. The activity of Ang-2 depends on circumstances; in the absence of VEGF it leads to vascular regression, but in the presence of high VEGF concentration it stimulates angiogenesis. The rapid tumour cell proliferation causes local hypoxia. Hypoxia-inducible factor (HIF-1a) stimulates synthesis of angiopoietins, especially Ang-2. Undoubtedly angiopoietins participate in regulation of tumour angiogenesis, but results of studies carried out so far, both experimental and clinical, are unclear or contradictory.